Automated method for concurrent determination of thorium (230Th, 232Th) and uranium (234U, 235U, 238U) isotopes in water matrices with ICP-MS/MS. Issue 4 (28th March 2022) - Ni, Youyi; Bu, Wenting; Ding, Xiaotong; Xiong, Ke; Wang, Hailong; Yang, Chuting; Hu, Sheng; Men, Wu
Abstract : High-efficiency analysis of Th and U isotopes are important technical issues encountered in the fields such as environment monitoring and nuclear emergency responses. Abstract : High-efficiency analysis of Th and U isotopes are important technical issues encountered in the fields such as environment monitoring and nuclear emergency responses. Here, we have proposed a novel automated method for the concurrent determination of Th ( 230 Th, 232 Th) and U ( 234 U, 235 U, 238 U) isotopes in small volumes (20 mL) of water matrices. A simple chemical separation procedure was achieved with an automatic system by employing UTEVA resin as separation material, and the final eluent was compatible with direct ICP-MS/MS measurement without any extra sample preparation. Recoveries of both Th and U exceeded 90% while repeatedly running the automated separation method 70 times; meanwhile, the background levels between sample intervals remained stable and minimized. The limits of detection (LOD) for all the target nuclides of the analytical method were less than pg mL −1 ; and the LODs of the minor isotopes 230 Th (0.02 fg mL −1 ) and 234 U (0.11 fg mL −1 ) were among the lowest ever reported, which was attributed to the effectiveness of the cleaning program of the automatic system and the non-interference determination of ICP-MS/MS. The merits of the analytical method were the ease of operation, good repeatability, low memory effect, and the high efficient recovery of both Th and U simultaneously. These features were advantageous for the large-scaled actual application of this method. The developed method was validated with several seawater and river water standard reference materials, where all the measured results of Th and U isotopes corresponded very well with the reference values. Finally, this method was further employed to determine Th and U isotopes in various types of real water samples and showed good practicability.